Development Status and Future Prospects of Strapdown Inertial Navigation Technology - Liu, Hongbo; Wu, Juncheng; Lin, Yuze; Yang, Xiaodong (Recent Advances in Electrical & Electronic Engineering, 2025)
BackgroundInertial navigation is a comprehensive technology involving precision machinery, computer technology, microelectronics, optics, automatic control, materials, and other disciplines and fields. Strapdown inertial navigation systems have gradually developed into the mainstream and direction of inertial navigation systems because of their small size, low cost, simple structure, and high reliability. The angular rate and acceleration information of the carrier relative to the inertial space are measured by the inertial measurement unit (IMU), and the instantaneous velocity and position information of the carrier are automatically calculated by Newton's law of motion. It has the characteristics of not relying on external information, not radiating energy to the outside world, not being disturbed, and good concealment. Therefore, it is widely used in aerospace, aviation, and navigation, especially in the military field.ObjectiveThis paper describes the development history of the Strapdown Inertia Navigation System summarizes the research status of the Strapdown Inertia Navigation System, and looks forward to its future development direction.MethodsThe key technologies of strapdown inertial navigation systems are investigated, and the related research on strapdown inertial navigation technology is understood in detail. The hardware composition and related algorithms of the strapdown inertial navigation system are analyzed in detail.ResultsNowadays, strapdown inertial navigation technology is the mainstream of inertial navigation technology. Compared with the gimbaled inertial navigation system technology, the strapdown inertial navigation system has higher precision, smaller volume, and lower cost. At present, the initial alignment technology, error compensation technology, navigation algorithm technology, and inertial device technology of strapdown inertial navigation technology have made full development.ConclusionWith the development of initial alignment technology, error compensation technology, navigation algorithm technology, and inertial device technology, the accuracy, response speed and anti-interference ability of strapdown inertial navigation technology have been significantly improved. The development of strapdown inertial navigation is closely related to the gyroscope technology which belongs to inertial device technology. The strapdown inertial navigation system based on optical gyroscopes such as laser gyroscopes and fibre optic gyroscopes is mature, and the MEMS strapdown inertial navigation system has a wide application prospect compared with the optical gyroscope strapdown inertial navigation system.
Keywords: Strapdown inertial navigation system